(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2017)
It is well established that the 1935 Italian invasion of Ethiopia was primarily aimed to take a revenge of the humiliation she experienced during the battle of Adowa, and a number of studies have chronicled the barbaric cruelty inflected by well-armed Italian army on ill equipped and untrained Ethiopian fighters. In spite of that, most research reports fail to reflect the historical facts regarding the attitude and the position of Pope Pius XI and the Vatican towards the Italo-Ethiopian conflict and the subsequent massacres. The present study seeks to examine real position and attitude of the Pope towarthe Italian invasion and massacre of its people for five years. To that end, many archives and historical documents have been used to collect data. A closer examination of archives reveal that Pope Pius XI has directly and indirectly supported Italian invasion of Ethiopia and her atrocities, and he never spoke out against what was clearly an unjust war. On June15, 1935, Pope Pius XI granted an audience to 7,000 veterans and celebrated a mass in their presence in an encouragement to the soldiers for massacre and an ideological support to Fascist Italy. On August 27, 1935 Pope Pius XI also granted an audience to an international congress of Catholic nurses at Castel Grandolfo and addressed them making special reference to the Italo-Ethiopian war as a distinct tribute of sympathy for Italy’s desire of colonization. In his expression “it is said in Italy that the war would be a just war because of the expansion of a population” the Pope clearly reflected Mussolini’s point of view and argument for his war against Ethiopia, and he seems to have believed that the war was just and, therefore, entreated only for “limits and moderation.” The Pope publicly expressed his joy at the victory of the Italian army over Ethiopia and described it as a “happy triumph.”Encouraged by the Pop’s position, most of the Catholic Bishops, Clergies and the Press strongly condemned the League of Nations for imposing sanctions against Italy and labeled the move as immoral. Members of the Italian hierarchy and the clergy apparently took a clear position in favor of the Italian war against Ethiopia and gave every possible support moral and material, to the Fascist leaders and army in their adventure of invading